Brain arteriovenous malformations - Łęczycka, Agnieszka (Przewodnik Lekarza/Guide for GPs, 2009)
Due to diversity of neurological symptoms of brain arteriovenous malformation (AVM) they can be frequently misdiagnosed. Excluding of presence of AVM should be considered in any case of neurological disorder that has sudden beginning or are chronic and don’t undergo any standard therapy.